In Search of the Midas Touch: Gold, Güiriseros and Globalization in Nicaragua - Aiyer, Ananthakrishnan (Anthropologica, 2022)
This paper seeks to interrogate three central claims of discourses on globalization—newness, interconnectedness, and the claim that capitalism is all pervasive in all parts of the world. Using historical and ethnographic materials from a mining town in Nicaragua, this paper explores these issues through a discussion of the changing relationships between small mining, gold production, and globalizing processes. It argues that the persistence of small mining and struggles over commodity production highlight the uneven and incomplete nature of capitalist globalization and the role of long-term historical processes in shaping contemporary local-global encounters. It concludes by suggesting a need for further theoretical refinement and a framework that incorporates older and newer approaches to the analysis of forms of commodity production under contemporary globalization.